Waste Awareness Campaign and Printer Donation - Rezki Alhamdi; Natal Olotua Sipayung; Dailami; Siska Amelia Maldin; Eryd Saputra; Wahyudi Ilham; Tito Pratama; Moh Thandzir; Syafruddin Rais (PUSLITABMAS-Politeknik Pariwisata Batamc, 2026)
This community service program (PKM) conducted by Batam Tourism Polytechnic at SMAN 3 Batam aimed to increase students' awareness of food waste reduction and support the teaching-learning process through a printer donation. The one-day activity involved 50 students and 5 teachers, utilizing interactive socialization methods such as presentations, videos, and small group discussions to address the causes, impacts, and solutions of food waste, followed by the handover of a multifunction printer with a technical demonstration. Qualitative evaluation through observation and informal interviews revealed that students significantly improved their understanding of food waste, actively participated in proposing practical solutions (e.g., taking adequate portions, utilizing leftovers), and expressed intentions to form a student-led waste management club, while the printer donation immediately facilitated the printing of teaching materials and assignments, reducing learning delays. This integrated approach combining environmental education with physical facility support, even in a short period, produced meaningful and sustainable impacts, aligning with SDGs 4 (Quality Education) and 12 (Responsible Consumption and Production).